ANALISIS KOMPETENSI KEPRIBADIAN GURU MATEMATIKA KELAS XI DI SMA NEGERI 1 ANDAM DEWI - Roslian Lubis; Eva Yanti Siregar; Deswati Simbolon (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The background of this research is that there are students who have difficulty understanding mathematics and the purpose of the research is to describe personality competence of mathematics teacher at the eleventh grade students of SMA Negeri 1 Andam Dewi. The approach of the research used descriptive qualitative. Questionnaire and interview used in collecting the data. The source of the data includes 10 students (5 students of XI MIA 1 and 5 students of XI MIA 2) and 2 mathematics teachers (1 teacher of XI MIA 1 and 1 teacher of XI MIA 2). Based on the questionnaire sheet shows 1) the average of personality competence of mathematics teacher of XI MIA 2 is 107.5 (good category) and 2) the average of personality competence of mathematics teacher of XI MIA 2 is 106.2 (good category). Furthermore based on interview, personality competence of mathematics teacher at the eleventh grade students of SMA Negeri 1 Andam Dewi is good category.